Studi Literature Review: Peran Kalimat Imperatif Dalam Novel Selena Karya Tere Liye - Andini Br Sembiring; Usiono Usiono (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
One type of literary work, the novel, is expected to benefit its readers by teaching them to pay attention to issues related to social life and encouraging them to behave well. Novels usually describe the reality of human life and its environment. This research focuses on imperative sentences in Selena Tere Liye's novels and what they mean. Qualitative descriptive data analysis method is used in this research. The data is collected through listening method, which is a note-taking technique. The results show that intrasitive imperative sentences exist in Tere Liye's novel Selena and have eight meanings. Among them are imperative sentences of request and demand, imperative sentences of hope, imperative sentences of prohibition and omission, imperative sentences of invitation, and imperative sentences of appeal. There are eighty important sentences from the data exposure and findings. The imperative sentence of request with 48 data is the most found, while the imperative sentence of omission with 2 data is the least.